Evaluation of Grain Yield and Agronomic Traits of Foreign Sesame (Sesamum Indicum. L) Genotypes under Drought Stress Conditions - M. Gholamhoseini; S. Mansouri; B. Masoudi; F. Shariati (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2022)
Despite the high potential of sesame production in the country, its yield and water use efficiency is low. Therefore, identifying genotypes with high grain yield, especially under drought stress conditions, is essential for developing this crop. For this purpose, field experiments were conducted to investigate the qualitative and quantitative response of 21 sesame genotypes to drought stress conditions at Seed and Plant Improvement Institute, Karaj, located in the semi-arid region of Iran, during the 2017 and 2018 growing seasons. The experiment was a split-plot based on a randomized complete block design with three replications. The irrigation treatments consisting of normal irrigation and drought stress were assigned to the main plots and the sesame genotypes (20 imported genotypes with one Iranian cultivar as a control) were allocated to the sub-plots. Dongeuy, Local 123, Hail 2 and Anthalya 1 genotypes were found as early maturing, Gynum 11, Kubarez 55, Uusu 1, Songhak, Hoechon 2, Dunae, Pachequero, Haibuk and Sunhua 1 genotypes as the medium maturing, Lao hong zhi ma, Bian gan, Bukbak, Margo, Amaliada, Jungkyung and Black chil sung genotypes as the late maturing and Oltan genotype as the very late maturing group. The Margo genotype showed the highest LAI (3.2), and Sunhua 1 genotype showed the lowest value (1.0). The results also revealed that drought stress decreased the number of capsules per plant, the number of seeds per capsule and 1000-seed weight by 35, 44 and 35%, respectively. On the other hand, drought stress caused a reduction in grain and dry matter yield in all genotypes. The Dongeuy genotype with 50% reduction and Songhak genotype with 26% reduction in grain yield showed the highest and lowest sufferings from drought stress, respectively. The Margo genotype produced the highest grain yield in both irrigation treatments (1531 and 1107 kg ha-1 under normal irrigation and drought stress treatments, respectively). In conclusion, the Songhak genotype was considered as one of the superior genotypes due to its shorter growing period, less grain yield loss under drought stress, and high oil yield.